TINJAUAN YURIDIS TERHADAP PENERAPAN PASAL 5 UNDANGUNDANG NOMOR 15 TAHUN 2002 TENTANG PENCUCIAN UANG DALAM PENETAPAN TERSANGKA EDDIES ADELIA - Andri Siburian, Tedi Franggoes; Edorita, Widia; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The problem of money laundering in Indonesia is no longer a new problemin matters of law and economics. Its growth continues to increase from year toyear, Quality Money Laundering done more neatly and systematically not onlythreatens the stability and integrity of the economic system and the financialsystem, but also can harm the joints of the life of society, nation and state.Development of anti-money laundering regime in Indonesia that began since theadoption of the Law of the Republic of Indonesia Number 15 Year 2002 on MoneyLaundering as amended by Act of the Republic of Indonesia Number 25 of 2003and the last by Law of the Republic of Indonesia Number 8 Year 2010 onPreventing and Combating Money Laundering. One example is the case of moneylaundering Eddies Adelia Artist of money alleged corruption committed by herhusband Ferry Setiawan. Purpose of this study, namely: the first to determine thechronology of the case Eddies Adelia, secondly, to determine the criminalresponsibility of the wife in money laundering.This type of research is a normative legal research, the study of theprinciples of law that starts from certain areas of the rule of law. Analysisconducted in this study is qualitative analysis to draw conclusions deductively iedrawing conclusions from things that are common to the things that are special.The survey results revealed that the chronological case begins EddiesAdelia set as suspect cases of money laundering. He allegedly received fundsamounting to Rp 1,000,000,000.00 (one billion dollars) as many as 10 times amonth, the fund flow from her husband's Ferry Setiawan, suspected cases offraud, embezzlement, and money laundering, with a mode of investment fundsrelated to the procurement of coal. Police investigators suspect the flow of fundswas the result of a crime Ferry Setiawan given to his wife. Eddies Adelia chargedunder Article 5 of Law No. 15 of 2002 on money laundering with a maximumpenalty of 5 years in prison and a maximum fine of Rp 1,000,000,000.00 (onebillion dollars) to account for his actions.Keywords: Application-Article- criminal act-money laundering